Evaluation Methodology for Graduate Follow-Up and The Development of Complex Competencies in Higher Education - Luna, Leny Bravo (Journal of Cultural Analysis and Social Change, 2025)
Graduate follow-up in higher education requires systematic and scientifically validated strategies to ensure educational quality and strengthen professional competencies. This study aimed to design an evaluation methodology to enhance graduate follow-up processes and promote the development of complex competencies in university professionals. A mixed-methods approach with an explanatory sequential design was adopted, combining qualitative and quantitative procedures. Semi-structured interviews were conducted with 20 experts in educational management, and structured questionnaires were administered to 46 graduates from a Human Medicine program at a private university in Lima. Data collection techniques included interview guides, observation, and surveys. Qualitative data were analyzed through thematic coding, while quantitative data were processed using descriptive and inferential statistics. The results confirmed the theoretical validity of the proposed graduate-tracking metamodel, highlighting its coherence, relevance, and capacity to generate reliable information about graduates’ professional trajectories. Quantitative findings revealed weaknesses in self-information, self-training, and self-development competencies, as well as insufficient preparation to meet the demands of the labor market. The integration of the complex competencies approach emerged as a key component for guiding curricular improvements and reinforcing employability. In conclusion, the proposed methodology proved effective for evaluating and monitoring the development of complex competencies in university graduates, enabling continuous feedback on curricula and strengthening institutional processes for educational quality assurance.